Development Of A Material Delivery System Of 3d Printing Used For Building Construction - Wong, Ci Qian (Universiti Sains Malaysia, 2019)
3D printing is a modern manufacturing technology. This technology builds 3D models from stacking of 2D layers. The application of 3D printing in the sector of building construction is an emerging technology. It provides advantages over the traditional construction method in terms of time, cost, waste reduction and architectural freedom. Application of 3D printing in construction requires technological integration of various systems. One of the important systems involved is material delivery system. Currently, there is limited research that focused on the material delivery system. This project aims to develop a material delivery system of 3D printing used for building construction. The material delivery system is designed schematically. Then, a model of the nozzle assembly is designed and fabricated. The relationship between the nozzle speed, flow rate and storage tank size are derived. Test carried out using the fabricated model shows that the working of the material delivery system depends greatly on material properties. The material delivery system can produce desirable extrusion with suitable material. It has the potential to serve as a blueprint for 3D printing construction projects or research that require a material delivery system for extruding an available suitable material.